Identificação dos elementos terras raras na região do Ajarani/ Campos Novos - Truquete, Melanie Kaline (2013)
In this work will be presented and results of X-ray diffraction and scanning electron microscopy coupled with an energy dispersal in soil samples collected in five specific areas, from the results of radiometric anomalies in vicinal -03 region of Ajarani in order to identify the assembly with a special mineral carriers of the rare earth elements. Studies focusing on the identification of Brazilian soils with these potentials are important, since these elements are drivers of different technologies, with various applications, ranging from metals to agriculture and tu al men - you, the cost of importing these minerals has increased significantly, the target of interest to developed countries, leveraging intense search for new deposits. The technique of X-ray Diffraction is the incidence of X-rays over a crystalline sample, making possible microstructural characterization, allowing instrumental parameters using the analogy with the records cataloged each mineral. Treating the detailing of these samples from semiquantitative analysis, the technique of scanning electron microscopy back-scattered electron (SEM / BSE) made ˆaˆait possible to identify the chemical elements contained in the samples. The results show that there is occurrence of rare earth elements in the studied areas, however the diffraction results do not indicate the phases of these minerals, moreover, suggest the presence of major soils forming minerals derived from igneous and metamorphic rocks, which reflects the local geology.